VALUASI JUMLAH AIR DI EKOSISTEM LAHAN GAMBUT DENGAN DATA LANDSAT 8 OLI/TIRS (WATER CONTENT VALUATION IN PEATLAND ECOSYSTEM BY USING LANDSAT 8 OLI/TIRS) - Idung Risdiyanto; Alan Nur Wahid (Indonesian National Institute of Aeronautics and Space (LAPAN), 2017)
The water content of peatland ecosystems stored as gasses in the air and as liquid in the peat soil and vegetation. The presence of water was influential to the value of spectral radians received by satellite sensors. Objective of study were develop empirical model to be applied in the Landsat 8 satellite imagery interpretation to estimate water content of peatland ecosystem. Method consisted of field measurements and satellite data interpretation. Field activities aimed to obtain weather parameters such as radiation, air temperature, surface temperature, evapotranspiration (ET), relative humidity (RH), soil water content (KAT), and biomass for each land cover in peatland ecosystems. Field measurements results were used to validate the parameters derived from Landsat 8 satellite data. Water content in the air was assessed by the ET and RH, in the soil was assessed by soil heat flux (G) and in the vegetation by biomass. The results of the validation of the data field measurement with Landsat 8 showed only ET (r2 = 0.71), RH (r2 = 0.71), and biomass (r2 = 0.87) had a strong relationship, while between G and KAT had weak relationship. Conclusion of this study indicated Landsat 8 satellite data could be used to calculate the water content in the air and vegetation. Thus, estimating water content in the peatland ecosystem with satellite data can only be done on the surface. AbstrakEkosistem lahan gambut menyimpan air dalam bentuk gas di udara, dan cair dalam tanah gambut dan vegetasi. Keberadaannya mempengaruhi nilai spektral radians yang diterima oleh sensor satelit. Tujuan penelitian ini adalah untuk mendapatkan model empirik yang dapat diaplikasikan untuk interpretasi citra satelit dalam pendugaan jumlah air di ekosistem lahan gambut. Metode penelitian terdiri dari pengukuran lapangan dan interpretasi data satelit LANDSAT 8. Parameter cuaca seperti radiasi, suhu udara, suhu permukaan, evapotranspirasi (ET), kelembaban udara (RH), kadar air tanah (KAT) dan biomassa diukur di lapangan pada setiap jenis tutupan lahan. Hasil-hasil pengukuran lapangan digunakan untuk memvalidasi parameter-parameter yang diturunkan dari data satelit LANDSAT 8. Jumlah air di udara yang dinilai dari ET dan RH, jumlah air di tanah dinilai dengan laju pemanasan tanah (G) dan jumlah air di vegetasi dengan biomassa. Hasil validasi antara data lapangan dengan data LANDSAT 8 menunjukkan hanya nilai ET (r2=0,71), RH (r2=0,71), dan biomassa ((r2=0,87) mempunyai hubungan yang kuat, sedangkan nilai G tidak mempunyai hubungan yang kuat dengan KAT. Penelitian ini menyimpulkan bahwa data satelit LANDSAT 8 hanya dapat digunakan untuk menghitung jumlah air yang tersimpan di udara dan vegetasi. Oleh karena itu, pendugaan jumlah air di ekosistem lahan gambut dengan data satelit hanya dapat dilakukan di atas permukaan.